1993
DOI: 10.1093/oxfordjournals.humrep.a137963
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy: Transvaginal crown—rump length measurements of 224 successful pregnancies which resulted from gamete intra-Fallopian transfer or in-vitro fertilization

Abstract: The crown-rump lengths (CRL) of 224 pregnancies which resulted from gamete intra-Fallopian transfer (GIFT) or in-vitro fertilization (IVF) were assessed two to four times in the first trimester. The results were compared with some of the published articles which assessed CRL in spontaneous and induced pregnancies. The range of CRL measurements from this study was generally smaller than the previously published data, although all women went on to deliver normal fetuses at full term weighing > 2.5 kg. It was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, the evaluation by Carnegie staging system is not commonly used in early pregnancy, and according to the indirect evidence from ultrasound monitoring of intrauterine embryonic size, the embryonic size variation in very early stage of pregnancy is not negligible; whilst after 46 days of embryo development, the fetal sizes in different studies becomes consistent 24, 25. The early embryonic size variation reduced in pregnancies from assisted reproduction with subsequent normal live birth 26, 27. While in general early pregnancy group with unknown outcome, the variation remained obvious 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation by Carnegie staging system is not commonly used in early pregnancy, and according to the indirect evidence from ultrasound monitoring of intrauterine embryonic size, the embryonic size variation in very early stage of pregnancy is not negligible; whilst after 46 days of embryo development, the fetal sizes in different studies becomes consistent 24, 25. The early embryonic size variation reduced in pregnancies from assisted reproduction with subsequent normal live birth 26, 27. While in general early pregnancy group with unknown outcome, the variation remained obvious 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the original formula was derived in 1975 from a study of 334 singleton pregnancies in women with regular menstrual cycles and certain LMP, several subsequent studies have generally confirmed the accuracy of the prediction [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Some studies, however, have suggested that in pregnancies below 8 weeks, the measurement of CRL underestimates the GA [17,25] . Studies reporting reference ranges for embryonic HR, GSD or YSD have examined small numbers of either spontaneously conceived pregnancies in women with certain LMP or in vitro fertilisation pregnancies and reported their values either in relation to GA or embryonic CRL [14,18,26, .…”
Section: Introductionmentioning
confidence: 99%
“…The searches yielded 1142 citations, of which 62 were considered for potential inclusion (Figure ). Thirty‐three studies were excluded because they described growth with GA ( n = 16), assessed or compared existing chart(s) ( n = 3), were reviews or practice guidelines ( n = 3), or had other aims ( n = 11; Table S2) . Finally, 29 studies providing data on over 11 000 pregnancies met the inclusion criteria and were included in the final analysis (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…A number of studies reporting CRL measurements in the first trimester have been excluded from this review because they attempted to answer a different question: to describe fetal growth in the first trimester . In some of the studies the authors considered both of these concepts, and such reports were included if GA estimation was one of the stated aims of the study and if a GA estimation formula was provided, regardless of how the data were analysed .…”
Section: Discussionmentioning
confidence: 99%